Design and modeling of power transistor-assisted sen transformers for transmission grid power flow control - Hassan, Salah Eldeen Gasim Mohamed (2017)
Many arising factors endanger the secure and stable operation of transmission grids. Those are deregulation that opens transmission grid, increasing dynamics in consequence of wide integration of variable renewable energy sources, unwillingness to install new transmission lines, electric power demand increase, resulting stress that causes frequent components outage, uneven distribution of power in transmission lines, and resulting low utilization of existing transmission grid infrastructure. In consequence, the need to widely use transmission grid power flow controllers is escalating. However, these power flow controllers need to be reasonably costing as well as technically competent. Three main families of existing power flow controllers are conventional power flow controllers, flexible AC transmission systems controllers, and hybrid power flow controllers, which all have their pros and cons. Conventional power flow controllers are cost-effective, however, have technical shortcomings. Flexible AC transmission systems controllers are technically competent but their cost is high. Hybrid power flow controllers combine some advantages of the other two families, however, have their own limitations, and their cost is still high. Combination of most technical advantages of existing power flow controllers in a single power flow controller at a reasonable cost is promising. Based on a comprehensive review, a family of power transistor-assisted Sen Transformers that bridges the gap between unified power flow controller and Sen Transformer is proposed. Power transistor-assisted Sen Transformers are designed and their comprehensive Simulink model is developed and tested in MATLAB/SIMULINK. Ratings of components of a power transistor-assisted Sen Transformer are determined and its cost is analyzed and compared to that of a similar unified power flow controller. Operation principle of power transistor-assisted Sen Transformers, operational characteristics, and control strategies are revealed. Also, a simplified Simulink model and a comprehensive Newton-Raphson model of power transistor-assisted Sen Transformers are developed and validated. Performance of power transistor-assisted Sen Transformers for enhancement of optimal power flow and also for maintaining grid security is assessed and compared to that of Sen Transformer and unified power flow controller.